Endoscopic resection of lateral spreading tumours in the distal descending segment of duodenum: a rare case report - Yao, Qi; Ji, Xingming; Wang, Ye (Journal of the Pakistan Medical Association, 2025)
This case reports a patient whose chief complaint was black stool for one month. The white light endoscopic image showed a lesion in the distal proximal horizontal part of the descending duodenum, identified as laterally spreading tumours, non-granular type, flat-elevated type (LST-NG-F). The pathological diagnosis was tubular villous adenoma with high-grade intraepithelial neoplasia. Endoscopic narrow-band imaging revealed disordered mucosal glandular duct openings, disrupted mucosal microvascular arrangement, and a clear boundary between the pathological tissue and the surrounding tissue. After obtaining informed consent, the surgical resection was performed using a treatment strategy involving rubber band ligature and electrotomy. A resection specimen measuring 1.4×2cm was obtained, with negative postoperative resection margins. Keywords: Duodenal tumour, adenoma, intraepithelial neoplasia, digestive system endoscopic surgery.